2005
DOI: 10.3354/meps304179
|View full text |Cite
|
Sign up to set email alerts
|

Generalized system of imposex and reproductive failure in female gastropods of coastal waters of mainland China

Abstract: We investigated the occurrence of imposex in gastropods from the coastal waters of mainland China from November 1999 to July 2004. Imposex was found in 30 species from 8 families, and was recorded in 20 species for the first time. In addition to the already known phenotypes of imposex expression in Cantharus cecillei, we also found aborted egg capsules in specimens with a split ventral channel (stage and type classification: S 6c* ) and various extensions of the proximal vas deferens (PVD). The PVD went up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 58 publications
2
63
0
4
Order By: Relevance
“…More than 150 molluscan species worldwide were affected by the endocrine modulation induced by TBT. Deriving from laboratory experiments and in situ studies it was evident that the endocrine effects could be induced at extremely low concentration of 0.1 ng/L TBT (Oehlmann et al 2007;Shi et al 2005). In most species TBT is able to induce a phenomenon called imposex, the appearance of male sexual characteristics in females.…”
Section: Tributlytin Compoundsmentioning
confidence: 99%
“…More than 150 molluscan species worldwide were affected by the endocrine modulation induced by TBT. Deriving from laboratory experiments and in situ studies it was evident that the endocrine effects could be induced at extremely low concentration of 0.1 ng/L TBT (Oehlmann et al 2007;Shi et al 2005). In most species TBT is able to induce a phenomenon called imposex, the appearance of male sexual characteristics in females.…”
Section: Tributlytin Compoundsmentioning
confidence: 99%
“…10,11 Por outro lado, é sabido que alguns países em desenvolvimento seguem utilizando estes compostos. 12 Em razão dos problemas ambientais associados ao uso de tintas à base de organoestânicos e seu gradativo banimento mundial, uma terceira geração de tintas anti-incrustantes começou a ser utilizada a partir de 1987. Esse novo grupo de tintas contempla atualmente 16 diferentes compostos biocidas que estão homologados pela IMO para utilização em embarcações (Tabela 1).…”
Section: Introductionunclassified
“…Many countries have developed methods that use imposex status of native gastropods to predict contamination of aquatic environments. Imposex of gastropods in China has been widely observed in organotin-polluted coastal waters (Shi et al, 2005), however, few cases have been reported which used this phenomenon for biological monitoring. The following reviews the preliminary research about species that have been considered for biomarker candidates in China in the future.…”
Section: Monitoring Tbt In Marine Environments Using Biomarkersmentioning
confidence: 99%
“…In total, imposex has been documented in over 150 gastropod species (Matthiessen et al, 1999). In the coastal waters of China, imposex of gastropods is a widely reported problem related to organotin pollution (Shi et al, 2005). Indeed, among the countries of the world, Asia is one of the most organotin contaminated, where imposex has been shown in 100% of oysters in some ports of Taiwan and Japan (Sun et al, 2005).…”
Section: Accumulation Of Organotins In Marine Biotamentioning
confidence: 99%